Markers of chronic disease risk in a cohort of Aboriginal children: findings from the Study of Environment on Aboriginal Resilience and Child Health (SEARCH). (14th October 2021) - Riley, Tamara; Lovett, Raymond; Banks, Emily; Thandrayen, Joanne; Sherriff, Simone; Muthayya, Sumithra; Spokes, Leigh; Wright, Lachlan; Thurber, Katherine A.
Abstract: Objective : This study investigated chronic disease risk markers among a cohort of Aboriginal children in New South Wales. Methods : Distributions of body mass index (BMI), blood lipids and haemoglobin A1c (HbA1c) among Aboriginal children aged 5‐<19 years were investigated. Prevalence ratios (PR) were calculated for borderline/high total cholesterol, low‐density lipoprotein (LDL) cholesterol and HbA1c, and low high‐density lipoprotein (HDL) cholesterol, by age group, sex and BMI. Results : Almost half (46.8%) of the cohort, had a normal BMI and 53.3% had overweight or obesity. Prevalence of chronic disease risk markers was low, with no individuals having high total cholesterol (0.0%) and few having high LDL (3.0%) or borderline/high HbA1c (2.6%); 85.5% of the cohort had normal HDL. There was no significant variation in the prevalence of chronic disease risk markers by age group or sex. The prevalence of borderline total cholesterol was 28% higher (PR 1.28, 95%CI 1.06‐1.54), and the prevalence of low HDL was double (2.00, 1.19‐3.35) for participants with obesity versus normal BMI. Conclusions : Dyslipidaemia and elevated HbA1c prevalence was low in the cohort, increasing with high BMI. Overweight and obesity were common, which increase the risk of developing chronic disease later in life. Implications for public health : Findings indicate few Aboriginal children have dyslipidaemia and hyperglycaemia, supporting screening for chronic disease risk factors from 18 years of age. Opportunities to reduce overweight and obesity among children should be considered to decrease the future risk of chronic disease.